Peningkatan Pengetahuan Studi Etnomedisin Pada Mahasiswa Farmasi - Nisa Isneni Hanifa; Agriana Rosmalina Hidayati; Anggit Listyacahyani Sunarwidhi; Dyke Gita Wirasisya (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
The topic of research on the exploration of natural materials is still a favorite among pharmacy students. This is also supported by the biodiversity in Indonesia which is spread across the region. Students need more insight and description of research topics related to natural product products, one of which is ethnomedicine studies. Based on this background, it is necessary to provide education related to ethnomedicine studies from experts to increase students' knowledge about the topic of exploring medicinal herbs and plants from ethnic groups in Indonesia. Education is carried out using lecture and discussion methods in webinars using virtual meeting applications with pretest and posttest. The webinar was attended by 239 participants, with the majority being pharmacy students from several Indonesian pharmacy universities. From the results of the pretest, it is known that the average knowledge of participants about ethnomedicine is 53.89. After the expert's explanation, the participants' knowledge increased with the average post-test score of 71.21. Participants' knowledge of the ethnomedicine study increased after being given education.